Penerapan Psikologi Arsitektur pada Fasilitas Pendidikan Anak Usia Dini dan Sekolah Dasar di Kota Surakarta - Tri Suci Hidayati; Tri Yuni Iswati; Leny Pramesti Pramesti (Universitas Sebelas Maret Surakarta, 2017)
Psychological architecture is a field of study that studies the relationship between built environment and human behavior, which mutually affect one another. The built environment and human behavior, especially in early childhood, will be closely related because in this period, children have not been able to develop their own potential, so that the environment will greatly affect the development of children’s potential. This study aims to know how the psychology of architecture applied in the Preschool and Elementary building. The application of psychological architecture in this building is done through the design in accordance with the children’s characteristics, by connecting the characteristics and theories of psychological architecture. The result of application can be seen in users, activities, site, space, and building mass. Keywords: psychological architecture, early childhood education, surakarta